Will Review for Points: The Unpaid Affective Labour of Placemaking for Google's 'Local Guides'. - Tarr, Alexander; Alvarez León, Luis F. (Feminist Review, 2019)
A growing number of people are relying on technologies like Google Maps not only to navigate and locate themselves in cartographic space but also to search, discover and evaluate urban places. While the spatial data that underlies such technology frequently appears as a combination of Google-created maps and locational information passively collected from mobile (GPS-enabled) devices, in this article we argue that for such systems to function as both useful tools for exploration for users and sources of revenue, users must actively produce massive quantities of granular spatial data that would otherwise be significantly more difficult and expensive to collect. The production of this qualitative information about places constitutes significant unremunerated affective labour. In this article, we build on the tradition of feminist geographies, especially feminist and critical Geographic Information Systems (GIS), to examine how the labour done by gendered, raced and often classed members of a local community is alienated by Google (i.e. Alphabet, Inc.) to produce commodified spatial data/media in the Local Guides platform. We analyse how Google's presentation of the platform hails women as care labourers—sharing their thoughts, feelings and knowledge of place for free in the name of supporting and caring for a community, however vaguely it may be constituted. At the same time, we argue that digital labour that produces the Local Guides platform draws from and reproduces specific gendering of spaces. We draw on a case study of a commercial corridor in the US city of Worcester, Massachusetts to show how the dialectic between affective digital labour and urban space has material effects on the production of raced, classed and gendered spaces and places. The article concludes with a call to maintain critical, feminist engagements with these types of platforms in order to further develop forms of digital praxis towards more just cities.